A numerical simulation study to evaluate the use of water alternating gas (WAG) as a pilot EOR method in Dulang Unit, Malaysia - Wan Sulaiman, Wan Rosli (2003)
Water alternating gas (WAG) injection schemes have become an important strategy to enhanced oil recovery (EOR) around the world and has been the focus of interest in recent years in Malaysia. S3 block El2114 reservoirs of Dulang Unit were selected as a pilot project to evaluate the feasibility of EOR using immiscible WAG injection. This block had been producing for the last 11 years and has had water injection for the last 6 years. The study commenced with the analysis of all pertinent data on the reservoir that were used as an input into the model. The production data were updated from February 2000 until December 2002 by incorporating additional pressure, production and injection data. The input data were fine-tuned by history matching studies before proceeding with the prediction runs. Based on current well performance, maintaining current operating strategy gave a total ultimate recovery of 10.9 MMstb at the end of 2020 which represents an average oil recovery factor of 33.7%. Two candidates for WAG injector, DULAOlOL and DULA002L in this block were accessed on its performance to sweep the oil. Studies conducted indicate that converting well DULA002L into WAG injector was the best scenario which gave additional 1.2 MMstb of oil. Total oil recovery under this scenario was predicted at 37.4% after 29 years of production. In order to obtain an optimum WAG injection cycle length, five different sensitivity cases were studied and showed that injection of gas for 90 days and followed by water for another 90 days was the best case for piloting this block. This gave a gas to water ratio of 1 : 1.